Healthy, wealthy and wise: the benefits of chemical research. (1st June 2015) - Phillips, David
Chemistry is the great enabling subject that is central to progress in solving global problems. In today's world, these problems are as vital, as new energy sources, food, clean water, and healthcare. David Philips presents some current research in these areas as well as his own work in the field of targeted photodynamic therapy of cancer.